Geochemistry and geochronology of S-type granites and their coeval MP/HT meta-sedimentary rocks in Chinese Southwest Tianshan and their tectonic implications - Gou, Long-Long; Zhang, L.; Lü, Z.; Shen, T. (Pergamon-Elsevier Science Ltd, 2015)
© 2015 Elsevier Ltd. This paper presents whole-rock geochemical data, in-situ zircon U-Pb ages and Hf isotopic composition, monazite U-Th-Pb age and pseudosection modeling result, in order to reveal the genetic relationship between S-type granites and meta-sedimentary rocks in the Central Tianshan and their tectonic implications for the South Tianshan Orogenic Belt. The S-type granites have the LA-ICP-MS zircon U-Pb ages of 275±3Ma, 266±13Ma and 278±3Ma, interpreted as the crystallization ages. They have high contents of SiO2 (72.41-83.24wt.%) and K2O (2.96-8.47wt.%) and low contents of Fe2O3t (0.61-2.19wt.%), MgO (0-0.49wt.%) and CaO (0.61-1.51wt.%), with A/CNK ratios of 1.14-1.35. The SHRIMP zircon U-Pb dating for the metapelite yields a weighted mean 206Pb/238U age of 393±7Ma and a significantly younger apparent 206Pb/238U age of 267±6Ma, whereas the EMP monazite dating gives three age groups, including 482±19Ma, 366±10-376±13Ma, and 282±17Ma. Two metamorphic events are identified, one is the regional anatexis event at ca. 393Ma based on the recent published result, which may be related to the arc magmatism, and the other is an anatexis event at ca. 280Ma in the post-collisional setting. Pseudosection modeling shows that the meta-sedimentary rocks have experienced the anatexis under a P-T condition of 7.21kbar and 728°C, consistent with medium-pressure facies series. Thus, the meta-sedimentary rocks are inferred to have been buried to the depths of middle-to-lower crust through the crustal thickening during the continental collision at ca. 320-300Ma, and then these rocks experienced the anatexis to form the S-type granites in the post-collisional setting with the heat possibly provided by the upwelling of asthenosphere and crustal thinning.